Peran Pondok Pesantren dalam Mencegah Faham Radikalisme di Pondok Pesantren Al-Ma’ruf Lamongan - Siti Suwaibatul Aslamiyah (Kuttab : Jurnal Ilmu Pendidikan Islam, 2020)
This research entitled The Role of Islamic Boarding Schools in Preventing Radicalism in the Al-Ma'ruf Lamongan Islamic Boarding School, in this study there are several things that will be examined, namely 1) the role of teaching in the Al-ma'ruf Islamic boarding school in preventing radicalism? 2) the role of kiai in the Al-ma'ruf Islamic boarding school in preventing radicalism? The researcher used qualitative methods and a case study approach. The results of the research of the subjects studied were first through the role of teaching books to understand religion, then the inculcation of disciplinary values, methods and aspects of the curriculum used in the Al-ma'ruf Islamic boarding school based on books or books that teach the values of understanding. moderate Islam, and the cultivation of the ideology of Ahlussunnah Wal jama'ah Annahdliyah (NU), the two roles of the kiai as role models, the kiai as advisors, and the Kiai as guides, hereby researchers want to know about the Role of Islamic Boarding Schools in Preventing Radicalism in Islamic Boarding Schools Al -Ma'ruf Kranggan Sidokumpul Lamongan.